Applicability of the Project Model Canvas tool for project management at school: practical workshops of the national inclusive policy in teacher training (Research, Society and Development, 2022)
The aim of this study is to present the model Canvas project (PMC) as a technological support tool for planning inclusive workshops in teacher training. Workshops at school based on the practice of the national policy on special education from an inclusive perspective. The research methodology is of a qualitative nature, with an analysis of the educational policy of inclusion, its regulations and the subjects of this process. The application will be in a school in the municipal network of Fortaleza of Elementary Education I and II, a school that has a Multifunctional Resource Room (SRM) and a Teacher of Specialized Educational Assistance (A.E.E), the workshops will take place in three moments in a hybrid way. The research presents a documental analysis of the 1988 Constitution, LDB 9394/96, National Policy on Special Education in an Inclusive Perspective, scientific articles on PMC Canvas model project and teacher training for Inclusive Education. Results: the PMC brings significant contributions to its use at school, being a beneficial tool in communication, clarity and objectivity that can streamline construction processes and project management. Although the research is ongoing, given the results achieved so far, it is concluded that the PMC in the educational area facilitates the articulation between the teacher of Specialized Educational Assistance and the teacher of the regular classroom, allowing to identify the justification and tangible objectives of the importance of inclusive workshops in the realization of the rights of students with intellectual disabilities, it was allowed to reflect on the use of strategies that help in the student's cognitive development and facilitate the teaching-learning process in the classroom.